2023
DOI: 10.3390/su15075827
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Recent Advancements in Absorption-Based Post Combustion Carbon Capture Technologies to Obtain a Sustainable Energy Sector with Clean Environment

Abstract: CO2 capture, use, and storage have been identified as significant strategies for reducing greenhouse gas emissions induced by the usage of fossil fuels. The current review focuses on the concepts of post-combustion capture technologies based on absorption mechanisms. Among all other developed technologies, researchers have proposed absorption as the most mature carbon capture technology for industrial-scale application. Absorption-based carbon capture can be classified into chemical and physical absorption, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…Therefore, the heat available after the solvent regeneration was used to heat the air and the syngas before the combustion chamber. The CO 2 capture process is characterised by the L/G ratio, which is the ratio of the flow rate of chemical solvent used to the flow rate of the syngas/flue gas [35,36]. It is also characterised by the amount of specific heat energy required in the chemical solvent regeneration process [37].…”
Section: Syngas Decarbonisationmentioning
confidence: 99%
“…Therefore, the heat available after the solvent regeneration was used to heat the air and the syngas before the combustion chamber. The CO 2 capture process is characterised by the L/G ratio, which is the ratio of the flow rate of chemical solvent used to the flow rate of the syngas/flue gas [35,36]. It is also characterised by the amount of specific heat energy required in the chemical solvent regeneration process [37].…”
Section: Syngas Decarbonisationmentioning
confidence: 99%
“…Similarly, the reaction mechanisms of alkanolamines, such as MEA with CO 2 , also yields carbamate, as shown below. CO 2 absorption using amine-based solvents involves a series of reactions, as illustrated in Figures 3 and 4 [35]. In Figure 3, the amine acts as a weak base, which reacts with acidic CO 2 to form carbamate.…”
Section: Alkanolaminesmentioning
confidence: 99%
“…Recent studies have revealed the promising potential of amino acid salt (AAS) as an alternative solvent. AAS solvents exhibit identical amine functionality, high chemical reactivity with CO 2 , better resistance towards degradation, and low volatility, and they are environmentally friendly [31][32][33][34][35]. Another unique feature of AAS is its ability to form a solid precipitate during reaction with CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of power and energy is increasing with accelerated commercialization and industrialization [ 1 ]. The continuous utilization of conventional fuels such as natural gas, oils, hydrocarbon gas liquids, fossil fuels and the severe environmental effect for using these materials raises serious concerns about the research of alternate energy resources [ [2] , [3] , [4] ].…”
Section: Introductionmentioning
confidence: 99%